ANALISIS KINERJA METODE K-NEAREST NEIGHBORS PADA DATA JOB FAIR - Purnamawati, Annida; Winnarto, Monikka Nur; Mailasari, Mely (Politeknik Bisnis Indonesia, 2024)
This study examines the performance of the K-Nearest Neighbors (KNN) method for classifying applicant data in data-driven job fair activities. The challenges faced include managing large volumes of applicant data and identifying optimal parameters for classification. The study uses a dataset containing 20,000 entries from Kaggle, with attributes such as skills, work experience, and completed projects. After data preprocessing, experiments were conducted using the KNN method with the Euclidean Distance algorithm, within a range of k values from 3 to 9. The results show that k = 3 provides the best performance with an accuracy of 65.00%, precision of 63.78%, recall of 71.88%, and an F1-score of 67.64%. The conclusion indicates that smaller k values capture local patterns better, while larger k values tend to reduce performance. This research contributes to the development of data-driven recruitment systems by enhancing the efficiency and accuracy of applicant selection. Further studies are recommended to explore additional optimization methods and feature combinations to improve classification accuracy.